Genetic Analysis of Oculocutaneous Albinism Type1A (OCA1A) in an Iranian Family - H Pour-Jafari; A Zamanian; B Pour-Jafari (Tehran University of Medical Sciences, 2010)
"nBackground: Oculocutaneous albinism type1 (OCA1) is characterized by the absence of melanin pigmentation. The mutation on TYR gene makes OCA1 as an autosomal recessive genetic disorder. In this study, we delineated the genetic analysis of an Iranian family with four members affected with OCA1. "nMethods: Clinical exams and paraclinical test were performed for all patients of the case family, also proband, her husband, and her parents. Pedigree chart was drawn too. We extracted the genomic DNA from the leukocytes of seven members of the family. Haplotype analysis at the TYR locus was done and informative microsatellite markers were employed. In order to amplify the entire coding region of the TYR gene, for bidirectional direct sequencing mutation analysis, eight sets of primers were used."nResults: Our patients were diagnosed as affected with Oculocutaneous albinism type1a. Analysis of pedigree pattern showed an autosomal recessive inheritance. Analysis with different markers in chromosomes 5, 6, 9, 11 and 15 showed that cause of albinism  in our case family was on chromosome 11 (D11S1887 marker was informative). "nConclusions: The results offered a more developed method of diagnosis for OCA1 carrier identification and genetic counseling for OCA1 affected families as well; also submit a sample of mutation involved with oculocutaneous albinism in Iran. Genetic analysis is necessary for determining the type of albinism in an individual patient.